2020
DOI: 10.2478/fon-2020-0029
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in new nurses: a qualitative study

Abstract: ObjectivesTo explore the resilience experience of new nurses and how new nurses develop and apply resilience strategies to cope with the difficulties during the transition period.MethodsA descriptive qualitative research method was on data acquired using data semi-structured interviews with 12 new nurses aged 20–26 years whose working time was more than 12 months but less than 24 months.ResultsAnalysis of the data could determine participants adopting resilience strategies to withstand difficulties and challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our findings build upon research examining emotional awareness and add value to the literature on resilience in these specific populations ( Hurley et al, 2020 ). We also make a noteworthy contribution to other qualitative research examining resilience in similar populations ( O'Dowd et al, 2018 ; Lyu et al, 2020 ). Our findings illustrate how emergency services personnel define emotional awareness and resilience, and what it means to them in the context of their work.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings build upon research examining emotional awareness and add value to the literature on resilience in these specific populations ( Hurley et al, 2020 ). We also make a noteworthy contribution to other qualitative research examining resilience in similar populations ( O'Dowd et al, 2018 ; Lyu et al, 2020 ). Our findings illustrate how emergency services personnel define emotional awareness and resilience, and what it means to them in the context of their work.…”
Section: Discussionmentioning
confidence: 87%
“… Ozdemir (2019) noted that athletes with high psychological resilience often had high subjective well-being, self-esteem, and a high stress threshold. Qualitative research conducted by Lyu et al (2020) suggested that developing resilience in nurses could alleviate high turnover rates. While research has continued to characterise resilience, popular culture has misconstrued the meaning of resilience: defining it as toughness, emotional control and recovering from difficulties without impact ( McGarry et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, during the transition period as new nurses adapt to their work, continuous interest and support are required on the part of hospitals. As part of the strategy suggested by Lyu et al [29], to enable new nurses to overcome physical and mental challenges, specific behavioral programs involving factors such as increasing optimism, building confidence, and expressing negative emotions are needed. Conversely, some new nurses sought a transfer to other departments to escape their difficult situation.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Researchers describe resilience as a set of dynamic attributes that includes an ability to face and recover from adversity, adapt to change, and adjust oneself and/or the environment while maintaining a positive attitude and optimism. [9][10][11] All individuals have the capacity to develop resilience, which is influenced by internal and external factors, including individual experiences, personal characteristics, the environment, and the person's balance of risk and protective factors. 10 Known as psychological capital, internal resilience-promoting qualities encompass a sense of purpose and self, faith, empathy, creativity, humor, high self-efficacy, flexibility, emotional intelligence, hope, and optimism.…”
Section: Background and Rationalementioning
confidence: 99%
“…Resilience by definition is “the ability to face adverse situations, remain focused, and continue to be optimistic for the future.”8 Studies illustrate that individuals, groups, and systems can develop resilience 9,10. Researchers describe resilience as a set of dynamic attributes that includes an ability to face and recover from adversity, adapt to change, and adjust oneself and/or the environment while maintaining a positive attitude and optimism 9-11…”
Section: Background and Rationalementioning
confidence: 99%